Comprehensive methodology for sample enrichment in EEG biomarker studies for Alzheimer’s risk classification - Verónica Henao Isaza; David Aguillon; Carlos Andrés Tobón-Quintero; Francisco Lopera; John Fredy Ochoa-Gómez (PLoS ONE, 2026)
Objective Dementia, particularly Alzheimer’s disease (AD), constitutes a major global health concern, with AD accounting for approximately 70% of all cases. EEG-based biomarkers hold promise for early identification of individuals at risk; however, small and heterogeneous samples frequently limit generalizability. Methods An EEG-based sample enrichment framework was developed by integrating advanced signal processing, component-level feature extraction, data harmonization (neuroHarmonize), and Propensity Score Matching (PSM). EEG data from four independent cohorts were harmonized to reduce site-related variability while preserving covariates such as age and sex. Features including power, entropy, coherence, synchronization likelihood, and cross-frequency coupling were extracted from independent components. PSM was applied at 2:1, 5:1, and 10:1 ratios to expand and balance the control group (HC) relative to the Alzheimer’s risk group (ACr), composed of PSEN1-E280A mutation carriers without cognitive symptoms. Results Sample enrichment through PSM improved classification accuracy, with decision tree models yielding values between 0.91 and 0.96. Higher enrichment ratios enhanced model stability and generalizability, as shown by learning curves and confusion matrices. Feature selection was based on model performance and effect sizes (Cohen’s d). Conclusions The proposed framework addresses sample size and variability constraints in EEG-based AD risk classification. Significance Harmonization and statistical balancing provide a replicable strategy for multicenter EEG studies targeting early AD detection.